Refrigeration property exploration of the superabsorbent hydrogel: Mechanism and application feasibility analysis. (July 2022) - Du, Zhaolin; Zhang, Zhihao; Chen, Hongan; Zheng, Tong
Abstract: A novel phenomenon that the phase equilibrium temperature (PET) of the poly (sodium acrylate) based superabsorbent hydrogel was lower than that of water was found, and its application potential in refrigeration was analyzed in this study. In addition, relations between the unit refrigerating capacity and apparent properties of the superabsorbent hydrogel, such as swelling ratio, cross-linking degree and neutralization degree, were investigated. Experimental results show that the PET of the superabsorbent hydrogel was lower than that of water. The hydrogel can achieve lower temperature than water and potentially be used as alternative refrigerant. Based on this, the superabsorbent hydrogel may have obvious advantages in improving the efficiency of absorption refrigeration cycle. The swelling ratio and cross-linking degree of the superabsorbent hydrogel had significant influence on its refrigeration capacity, whereas the neutralization degree had minimal effect. Finally, the application of super absorbent hydrogel as the refrigerant was attempted, and existing problems were analyzed. Graphical abstract: Image 1